Analisis Implementasi Pendidikan Moral Pancasila Sebagai Upaya Pencegahan Bullying di Sekolah - Anita Candra Dewi; Adniel Pascal Ancelo Jonas; Melinda Keizyah Mandaka; Nursia Nursia; Syahruwulida Muhammad; Ubaidir Rahman (Journal on Education, 2023)
Bullying among students has recently increased, particularly in primary and secondary schools. This shows a poor understanding of Pancasila. Therefore, further research and analysis is required to determine what measures should be taken if implemented in the future. Our analysis is descriptive and analytical in nature. The purpose of this study is to understand and explore the meaning, impact, prevalence, and ways to overcome bullying through a literature-based approach and theory of the consequences, prevalence, and elimination of bullying. The researcher suspects that teachers are reacting to the phenomenon of moral harassment in schools. This study also examines what to do in the event of violence